2018
DOI: 10.1161/jaha.117.007805
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Ca 2+ Influx Contributes to Arrhythmic Risk in Nonischemic Cardiomyopathy

Abstract: BackgroundHeart failure (HF) is associated with increased arrhythmia risk and triggered activity. Abnormal Ca2+ handling is thought to underlie triggered activity, and mitochondria participate in Ca2+ homeostasis.Methods and ResultsA model of nonischemic HF was induced in C57BL/6 mice by hypertension. Computer simulations were performed using a mouse ventricular myocyte model of HF. Isoproterenol‐induced premature ventricular contractions and ventricular fibrillation were more prevalent in nonischemic HF mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 54 publications
(108 reference statements)
0
43
0
Order By: Relevance
“…The overall ventricular myocyte model structure The spatiotemporal myocyte model ( Fig. 1 A) consists of a 3D coupled network of CRUs and mitochondria, modified from the model in our recent study (12), which contains 21,504 (64 Â 28 Â 12) CRUs and 5376 (64 Â 14 Â 6) mitochondria. These numbers can be changed for modeling different cell sizes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The overall ventricular myocyte model structure The spatiotemporal myocyte model ( Fig. 1 A) consists of a 3D coupled network of CRUs and mitochondria, modified from the model in our recent study (12), which contains 21,504 (64 Â 28 Â 12) CRUs and 5376 (64 Â 14 Â 6) mitochondria. These numbers can be changed for modeling different cell sizes.…”
Section: Methodsmentioning
confidence: 99%
“…1, B and C). The major improvements in the model from our previous study (12) are an incorporation of 1) a new, to our knowledge, stochastic MPTP gating model ( Fig. 1 F), a new, to our knowledge, model for mitochondrial Ca 2þ buffering, and simplified models for cytosolic ROS and ATP; 2) the MCU formulation by Williams et al (41) and the oxidized CaMKII signaling formulation by Foteinou et al (42) (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well-documented that a dramatically increased mitochondrial Ca 2+ level (i.e., mitochondrial Ca 2+ overload) causes cardiac dysfunction, mainly via cardiomyocyte death in various animal disease models [9,11,[147][148][149]. There are at least two key mechanisms by which elevated [Ca 2+ ] m promotes cardiomyocyte dysfunction and/or death: 1) mitochondrial ROS generation and 2) mPTP opening.…”
Section: Mitochondrial Ca 2+ Overload and Cardiac Pathologymentioning
confidence: 99%
“…For instance, cardiomyocyte-specific and inducible MCU deletion did not exhibit protective effects against surgical transverse aortic constriction [9,11], while pharmacological inhibition of MCU does provide some cardioprotective effects [153]. Xie and his colleagues used a non-ischemic heart failure model induced by hypertension resulting from unilateral nephrectomy, deoxycorticosterone acetate (DOCA) treatment, and addition of salt to drinking water and showed that cardiac mitochondria from this animal model has mitochondrial Ca 2+ overload and that pharmacological MCU inhibition or genetic MCU deletion protects the heart from early afterdepolarizations promoted by heart failure remodeling [148], though they used conventional MCU knockout mouse line [12] in this report. Elrod's group also showed that cardiomyocyte-specific and inducible NCLX deletion causes acute myocardial dysfunction and fulminant heart failure with a high incidence of sudden cardiac death [17].…”
Section: Mitochondrial Ca 2+ Overload and Cardiac Pathologymentioning
confidence: 99%